The Role of Family in Shaping Children's Gender Identity - Inayatul Ummah (Journal of Humanities, Social Sciences, and Education, 2025)
Gender identity is a crucial aspect of children's social development, influenced by various factors, one of which is the family. This literature review aims to analyze the role of family in shaping children's gender identity through parenting styles, social interactions, and cultural values instilled within the household. The findings indicate that parents play a primary role in shaping children's gender concepts through parenting practices, toy selection, and the division of domestic roles between males and females. Furthermore, family communication influences how children perceive gender norms and stereotypes in society. This study highlights the importance of parental awareness in adopting an inclusive parenting approach that does not limit children's potential based on socially constructed gender roles. In conclusion, the family has a significant impact on shaping children's gender identity, emphasizing the need for a more flexible approach that promotes gender equality within the family environment.